The Impact of Divergent and Convergent Tasks on Iraqi EFL Students Reading Comprehension Success - Sabeeha Hamza Dehham; Nadia Majeed Hussein (Sociometry Journal of Social Science, Art and Humanity, 2021)
This research attempted to explore the effects of divergent and convergent tasks on the successful reading of EFL students at the preparatory stage. To verify the analysis, the null hypothesis was established that states "There are no differences of statistical significance at the level of (0,05) among the mean of scores of the experimental group who study according to divergent and convergent task technique and the mean of the scores of the control group who study according to the regular method". The experimental approach is used by designing two equivalent experimental groups of 32 students studying the technique proposed, and an 8-week (2019-2020) control group of 32 students, three classes each week using the Google Classroom Platform and Telegram. The present study utilized the platform Google Classroom (GC) and Telegram as an educational platform to assist students during their course learning process. The writing skills test was administered after checking with the experts. The results show that there are statistical differences at level (0,05) between the average of the experimental and control groups' reading skills and those of the experimental group. This difference is because the experimental group uses divergent and convergent tasks.